Strategies for electrosynthesis of poly(vinylbenzyltrimethylammonium chloride) and composite films. Issue 4 (12th March 2017) - Zhang, Tianshi; Zhitomirsky, Igor
ABSTRACT: Poly(vinylbenzyl trimethyl ammonium chloride) (PVT) exhibits functional properties, which have generated interest in the fabrication of PVT and composite films. New electrochemical strategies have been utilized for the deposition of PVT-zirconia composites. The problems, related to the electrodeposition of strong polyelectrolytes, such as PVT, were addressed by the development of charge compensation mechanisms. The deposition strategies involved electrophoretic cathodic deposition (EPD) of PVT and EPD or electrochemical synthesis of zirconia. The proof of concept investigations involved deposition yield studies under different conditions, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential thermal analysis (DTA), and electron microscopy studies. The electrochemical strategies can be used for electrodeposition of various composites, utilizing the properties of functional polymers and inorganic materials.